Evaluation of the Efficiency of Long-Term Care Services in OECD Countries by DEA Method - Fevzi Akbulut; Osman Şenol; Ferit Sevim (Atatürk University, 2024)
Objective: This research aims to measure the efficiency of health services by using health indicators of OECD countries, to determine inefficiencies of countries that are not at the efficient border, to calculate idle use, and to determine super-efficiency values of countries at active borders.Methods: In the research, DEA was conducted using an input-oriented CCR model to measure the performance of the OECD countries in 2019, the last year before the pandemic. In the research, three input and two output variables were used. R Studio package programs were used for the analysis of research data.Results: It is seen that the productivity average of 15 countries is 0.81. 5 out of 16 countries have been identified as active. Finally, it has been determined that Hungary, with a super-efficiency value of 17.18, can still be on an efficient border even if it increases its input amounts 16 times.Conclusion: A notable observation is that some OECD countries with developed economies allocate substantial resources to long-term care services, and their capacities are at sufficiently high levels. It is recommended that low-productivity countries should reduce the idle use of input resources to increase their productivity.